Ideal Tenant Mix Composition Based on Consumer Preference Weighting Method In Travoy Hub Commercial Area - Joseph Mervin Oloan; Aswin D. Hadisumarto (Ridwan Institute, 2023)
The success of marketing activities and financial success in a commercial area or shopping center is influenced by several factors, one of which is the tenant mix factor. The process of analyzing the composition of the tenant mix using the consumer preference weighting method can make it easier for developers to know exactly the types of tenants expected and needed by potential consumers. The research object in this study is Travoy Hub, a commercial area that is being developed by PT Jasamarga Related Business. Specifically, there are three main parameters that can describe the tenant mix model effectively, namely the tenant preference category (Preferred Main Tenant Category), the tenant order category (Ranking of Main Tenant Category Preference), and the tenant product purchasing tendency category (Likelihood of Supporting Preferred Tenants). The aim of this research is to explain the logic of the research methodology as well as the preferences of potential consumers regarding tenant plans that will operate in the commercial area in question, using the example of a commercial area in the East Jakarta area.